Green Purchasing Behavior Analysis of Government Policy About Paid Plastic Bags - Muhammad Khoiruman; Aris Tri Haryanto (Universitas Pasundan, 2017)
This research will be conducted to know: 1) The influence of green perceived value to consumer green trust to use plastic bag after the policy of using plastic bag paid at modern retail store in Surakarta. 2) The influence of green perceived risk to consumer green trust to use plastic bag after the policy of using plastic bag paid at modern retail store in Surakarta. 3) The effect of green trust on green purchase behavior of consumers to use plastic bags after the policy of using plastic bag paid at modern retail store in Surakarta. The study was conducted in modern retail stores (Alfamart, Indomart and Superindo) in Surakarta using 200 respondents who shop at the modern retail store. A model that can be used to measure green purchasing behavior in the use of paid plastic bags using four interrelated variables: green perceived value, green perceived risk, green trust and green purchasing. Data analysis using Structural Equation Model (SEM). The result of analysis and discussion showed that green perceived value have positive and significant effect to green trust, green trust has positive effect on green purchasing, but green perceived risk has no significant effect to green trust.